The determinants of external auditors' independence for politically connected firms in Malaysia / I. K. Norziaton and Nurul Nadhirah Muharam - I. K., Norziaton; Muharam, Nurul Nadhirah (2021)
The auditing profession is a major concern for stakeholders and has been in a quagmire for the past years. To overcome the concern, client firms must take the initiative to assure that the management does not put pressure on the external auditors. Therefore, firms need to take part in positively influencing external auditors‟ independence to reduce the complexity of audit procedures, and consequently, improve external auditors‟ independence. Thus, the determinants of factors are needed to assure and maintain the independence of the external auditors at any time to perform their audit work. Hence, the main objective of this study is to examine the determinants of external auditors‟ independence among politically connected firms in Malaysia. The determinants are classified into two which are, first, auditor attributes namely, audit tenure and non-audit fee, and second, audit committee characteristics which consist of audit committee‟s independence and audit committee‟s diligence. Four hypotheses were developed and tested using a total of 46 sample firms from 2014 to 2018 with 230 firm-year observations. This study used secondary data from which the information was obtained from annual reports and DataStream. The results reveal that non-audit fee and audit committee‟s diligence influenced external auditors‟ independence, whereas audit tenure and audit committee‟s independence did not. Altogether, this study has provided useful information and implications for the professional bodies and Bursa Malaysia to help strengthen the principles of auditors‟ independence in politically connected firms.